Ultralow‐Expansion Lithium Metal Composite Anode via Gradient Framework Design. (26th June 2022) - Liu, Yucheng; Yuan, Boyu; Sun, Chuang; Lu, Yuhao; Lin, Xiaoping; Chen, Maohua; Xie, Yuansen; Zhang, Shanqing; Lai, Chao
Abstract: Improving the stability of lithium (Li) anodes is critical for the safety and reliability of Li metal batteries. Developing a 3D conductive Li host is suggested as one of the most promising strategies in this context, especially for suppressing the pulverization of the electrode. However, the material consistency and volume expansion of the electrodes (<15%) represent significant challenges for their applications in commercial pouch cells. In this work, dual‐gradient architecture, combining rigidity and flexibility through the synergistic effect of silver wires and carbon nanotubes, is fabricated by a facile suction filtration method. This unique network shows a volume expansion of only 5.4%, outperforming all previously reported composite Li anodes. In addition, the online digital holography clearly monitors the preferential deposition of metallic Li at the lithiophilic layer. Consequently, the present gradient host effectively prevents the deposition of metallic Li at the electrode/separator interface, resulting in excellent cycling stability in both symmetric and full cells. Abstract : Ultralow volume expansion of 5.4% is achieved using gradient network lithium host. Meanwhile, dendrite growth is well suppressed, and excellent cycling stability is also obtained even under a high current density up to 40 mA cm −2 induced by lithiophilic and highly conductive Ag nanowires.